2022
DOI: 10.32348/1852.4206.v14.n1.28987
|View full text |Cite
|
Sign up to set email alerts
|

Intervenciones neuropsicológicas para la recuperación funcional de niños y adolescentes con traumatismo craneoencefálico. Revisión sistemática

Abstract: El Trauma Craneoencefálico (TCE) pediátrico deteriora el funcionamiento cognitivo, afectivo y conductual de miles de menores en el mundo; sin embargo, los programas de rehabilitación parecen ser escasos. Esta investigación describe las intervenciones neuropsicológicas dirigidas a la recuperación de déficits cognitivos, conductuales y afectivos en menores de 19 años con TCE. Se realizó una búsqueda sistemática de artículos originales publicados en los últimos 5 años en las bases de datos Scopus y ScienceDirect,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 82 publications
0
0
0
Order By: Relevance
“…Thus, the results found are in line with the scientific literature that has also found that both forgiveness and gratitude are significant predictors of outgroup prosocial behavior, controlling for gender and age, and coincide with the few existing studies in this regard (García-Vázquez et al, 2020). Moreover, other cross-sectional studies conducted with Argentinean adolescents found similar results: the presence of positive emotions toward an aggressor was associated with prosociality and social commitment, but the absence of negative emotions toward an aggressor was not (Rodriguez & Moreno, 2022).…”
Section: Discussion Of the Second Goal Of The Papersupporting
confidence: 91%
“…Thus, the results found are in line with the scientific literature that has also found that both forgiveness and gratitude are significant predictors of outgroup prosocial behavior, controlling for gender and age, and coincide with the few existing studies in this regard (García-Vázquez et al, 2020). Moreover, other cross-sectional studies conducted with Argentinean adolescents found similar results: the presence of positive emotions toward an aggressor was associated with prosociality and social commitment, but the absence of negative emotions toward an aggressor was not (Rodriguez & Moreno, 2022).…”
Section: Discussion Of the Second Goal Of The Papersupporting
confidence: 91%